THE EFFECT OF PROBIOTICS ADDITION ON FEED TO THE GROWTH AND SURVIVAL OF TIGER GROUPER FISH (Epinephelus fuscoguttatus) - Erni Syafitri; Usman M Tang; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on February 9th until March 14th, 2016 took place in Batam Marine Aquaculture Centres located in Jl.Raya Barelang Bridge III P. Setoko PO.BOX. 60 Sekupang, Batam, Kepulauan Riau. The aim of this research is to know the growth and the survival rate of tiger grouper seed through the addition of probiotics in different doses. This research used experimental methods and one factor complete randomized design (CRD) with 4 treatments and 3 repetitions. The probiotics used in this research are probiotic P1 (0.5 g/kg feed), probiotic P2 (1.0 g/kg feed), probiotic P3 (2.0 g/kg feed) and probiotic P4 (No Extra probiotic as a control group). The best result of this research appeared on P3 treatment (2.0 g / kg feed) with the average weight of 76.50 g/head, the absolute weight of 36.20 grams, the absolute long of 16,56 cm, daily growth of 2.25% , and survival rate of 98.3%.Keywords: Probiotics ,Growth, Survival Rate, (Epinephelus fuscoguttatus).